Study on Overvoltage of Wind Farm Under AC Fault at Sending End of HVDC Transmission System - Wei LIANG; Linlin WU; Qiping LAI; Dongsheng LI; Man XU; Chen SHEN (Zhongguo dianli, 2023)
When the short circuit ratio of receiving end AC system is small, the fault disturbance of sending end AC system may cause commutation failure of the inverter and overvoltage at the LCC-HVDC sending end AC bus. This paper studies the mechanism and influencing factors of overvoltage at the point of common connection (PCC) of the wind farm caused by an AC fault at the HVDC sending end. Firstly, an electromagnetic transient model is established for UHVDC wind power transmission system. Secondly, the influence mechanism of the wind farm and HVDC dynamic characteristics on the transient voltage at the PCC of wind farm under different sending end faults is analyzed. Then, the factors affecting the transient voltage variation at the PCC of the wind farm are analyzed and verified by simulation. The results show that the variation of transient voltage at the PCC of the wind farm is mainly affected by the AC bus voltage of the rectifier station and the power response characteristics of the wind farm. In addition, it is found that the influence characteristics of wind farm capacity, wind speed, and other factors on the voltage at the PCC of wind farm are different under single change and different combinations.